THE IMPACT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) PRACTICES ON SUSTAINABILITY RISK OF BANKING COMPANIES LISTED ON THE IDX (2021–2024) - Reny Aziatul Pebriani; Vhika Meirisari; Yunita Maharani (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2026)
This study aims to analyze the relationship between Environmental, Social, and Governance (ESG) practices and sustainability risks in banking companies listed on the Indonesia Stock Exchange during the period 2021–2024. The study used a quantitative approach with panel-shaped secondary data obtained from the annual reports and sustainability reports of 18 banks, resulting in 72 observations. ESG practices are measured using a composite ESG index, while sustainability risk is constructed as a standardized deviation from environmental, social, and governance risk exposures, so that negative values reflect a relatively lower level of risk than the sample average. Data analysis was carried out using simple linear regression as an initial approach to identify patterns of statistical relationships between variables. The results showed that the ESG index was negatively and statistically significant with sustainability risk (? = –2.979; p < 0.05), with a determination coefficient value (R²) of 0.375. These findings indicate that stronger ESG practices tend to correlate with lower levels of sustainability risk, although they are not intended to draw strong causal conclusions. In the perspective of sharia economics, these empirical results are interpreted reflectively through the framework of maq??id al-shar??ah, in particular the principles of safeguarding benefits and sustainability, without claiming direct empirical testing of these normative values.